a) You can cancel (n-2)! from both. To demonstrate:
n! = n * (n-1) * (n-2) * (n-3) * .... 2 * 1
(n-2)! = (n-2) * (n-3) * .... 2 * 1
So, you can cancel out (n-2)! to get n * (n-1). You now have:
n(n-1) = 930
n^2 - n - 930 = 0
(n - 31)(n + 30) = 0
So, n = -30 or n = 31.
Since you can't have factorials of negative numbers, n must equal 31.
b) Write out the Permutations.
P(n, 5) = n!/(n-5)!
42 * P(n, 3) = 42n!/(n-3)!
Set them equal to each other.
n!/(n-5)! = 42n!/(n-3)!
You can cancel the n! to get:
1/(n-5)! = 42/(n-3)!
Examine what (n-3)! means:
(n-3)! = (n-3) * (n-4) * (n-5) * (n-6) *... * 2 * 1
You can see (n-5)! in there, so you know you can cancel (n-5)! to get:
1/1 = 42/(n-3)(n-4)
Get everything on one side to create a quadratic equation:
(n-3)(n-4) = 42
n^2 - 7n +12 = 42
n^2 - 7n - 30 = 0
(n - 10)(n + 3) = 0
So, n = 10 or n = -3.
Once again, we can't have negative solutions, so n must equal 10.